5-Methyl-N-(8-(5, 6, 7, 8-tetrahydroacridin-9-ylamino)octyl)-5H-indolo[2, 3-b]quinolin-11-amine: a highly potent human cholinesterase inhibitor12. Issue 6 (18th May 2017) - Wang, Li; Moraleda, Ignacio; Iriepa, Isabel; Romero, Alejandro; López-Muñoz, Francisco; Chioua, Mourad; Inokuchi, Tsutomu; Bartolini, Manuela; Marco-Contelles, José
Abstract : 5-Methyl- N -(8-(5, 6, 7, 8-tetrahydroacridin-9-ylamino)octyl)-5 H -indolo[2, 3- b ]quinolin-11-amine is a very potent human ChE inhibitor [IC50 (hAChE) = 0.95 ± 0.04 nM]. Abstract : The synthesis, cholinesterase inhibition, molecular modelling and ADME properties of novel tacrine–neocryptolepine heterodimers are described. Compound3 [5-methyl- N -(8-(5, 6, 7, 8-tetrahydroacridin-9-ylamino)octyl)-5 H -indolo[2, 3- b ]quinolin-11-amine], showing a moderate inhibition of the Aβ1–42 self-aggregation (26.5% at a 1 : 5 ratio with Aβ1–42 ), and a calculated log BB value (0.27) indicating excellent potential BBB penetration, is a highly potent human cholinesterase inhibitor [IC50 (hAChE) = 0.95 ± 0.04 nM; IC50 (hBuChE) = 2.29 ± 0.14 nM] which can be listed among the most potent hAChE inhibitors so far identified, and is not hepatotoxic in vitro at the concentrations at which the ChEs are inhibited. A molecular modeling study was also undertaken in order to elucidate the AChE and the BuChE bind modes of all the new compounds. The docking results show that all of them bind to AChE in extended conformations and to BuChE in folded conformations. Moreover, these studies revealed that the length of the linker is crucial to binding both the catalytic anionic site and the peripheral anionic site.